ISLAMIC EDUCATION REORIENTATION IN GROWING THE FITRAH GOODNESS IN THE ERA OF GLOBALIZATION - Nursaid, Nur Khozin (IAIN Ambon, 2019)
Abstract: The aim of the study was to find out how the position of Islamic education institutions in the era of globalization is transparent. Family institutions are the main foundation for the growth and development of today's generation. The role of the family is driven by both parents, the role of the school is driven by teachers, the community is motivated by community leaders and in universities driven by lecturers to foster religious nature in internalizing the faith and fostering a kindness of kindness. This study is a descriptive qualitative research approach that is to describe a phenomenon, event, event that occurred in the field. Data collection researchers used observation, then researchers also conducted activities Focus Group Discussion (FGD) is a form of data collection activities through group discussions and discussion in groups. Data analysis techniques use data reduction, data presentation, conclusion drawing. From this study it was found that there needs to be a reorientation of the vision and mission of Islamic education. with a big vision and mission that produces great output. If you want participants to return to their nature, then Islamic education in the process requires a great willingness to realize their vision and mission, so that the nature of goodness that exists in students can grow well as our human being. There needs to be a Reorientation of the Islamic Education Strategy that is needed to improve the quality and equity of education in all educational institutions. To foster fitrah, it is necessary to develop the character of the vision of ulul al-bab, al-ulama, al-muzakki, ahl al-dzikr, and al-rasikhuna fi al-‘ilm and position educators who are authoritative and have sacredness. It is necessary to optimize learning and internalize the main tasks of teachers as a profession, humanity, social quality of educators of Islamic education from various sides in the era of globalization. Keywords: Islamic Education, Fitrah Goodness, Era of Globalization